The ultra poor in the capital market - Halder, Shantana R.; Husain, A.M.Muazzam (Research and Evaluation Division, Brac, 2019)
This paper looks into the issue of accessibility of the capital market for the ultra poor by analyzing the extent of borrowing, their sources and uses of loan. One-fourth had access to any capital sources, and only about 5% received credit from any institutional sources. The landless, female-headed households, households depending only on female income, the wage-employed and the destitutes got less access to any kind of loan. On the other hand, access to loan had increased with increasing land. It was also higher for the households headed by male and for those depending only on male income. Endowment and personal networking with creditors were very important in getting access to any credit sources. Average interest rate paid for credit borrowed, irrespective of sources, was 17.92%. Nearly one-fifth of the total loan obtained from different sources was interest free. A maximum of 150% interest was also charged in Comilla and Jamalpur regions. Institutional loans were mostly used for investment and informal loan for crisis coping. The landless, female-headed households, wageemployed group and the destitutes, in most cases, borrowed to meet their emergencies and paid higher interest rate. Eighty-seven percent loan in Rangpur region were spent for crisis coping whereas in Camilla and Jamalpur a significant proportion of the loan was used for productive purposes.